King and Maxwell - Book 6 - Baldacci, David (New York : Grand Central Publishing, 2013)
"Sean King and Michelle Maxwell return in the latest blockbuster thriller from #1 New York Times bestselling author David Baldacci. Watch King & Maxwell, TNTs new series based on David Baldaccis blockbuster novels, on Mondays at 10 p.m. (ET/PT) "--
Keywords: King, Sean -- (Fictitious character); Fiction; Maxwell, Michelle -- (Fictitious character); Fiction; Private investigators -- Fiction; Security, International; Fiction; Thrillers (Fiction)